Національна інноваційна політика в умовах лібералізації зовнішньої торгівлі - Олефір, Андрій Олександрович; Олефир, Андрей Александрович; Olefir, Andrej (Одеса : Юрид. л-ра, 2014)
The article deals with the selection of conceptual towards the realization of national innovation policy analysis of the major gaps in enforcement strategies. An important part of it is devoted to the Ukraine’s economic integration into foreign market, economic and legal framework of this process. Also were critically examined the impact of economic globalization on national economic policies and made some recommendations of the state to protect the national interests.
Олефір А. О. Національна інноваційна політика в умовах лібералізації зовнішньої торгівлі / Олефір А. О. // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 233-245.
Keywords: національна інноваційна політика; зовнішня торгівля; глобалізація; інтеграція ринків; економічний суверенітет; национальная инновационная политика; внешняя торговля; глобализация; интеграция рынков; экономический суверенитет; national innovation policу; foreign trade; globalization; market integration; economic sovereignty